FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU AUDITOR DALAM PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT (Studi Empiris Pada Kantor Akuntan Publik di Batam dan Pekanbaru) - Desni Fellya; Raja Adri Satriawan Surya; Rheny Afri Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to analyze the influences of Time Pressure, Audit Risk, Materiality,Locus Of Control, Review Procedure and Quality Control and Etical Awareness to toward the premature audit prosedures sign off.The sample of this research came form of sixty correspondences who are Auditor who have worked on Public Accountant Office in Batam and Pekanbaru. Data collected through questionnaires are processed and analyze by using multiple regression analysis. The sampling method is purpossive sampling. The test for quality are using validity of test to use is pearson correlation and reliability test of the research to use is cronbach alpha. For hypotesis test, we are using Adjusted R square and t test. Data processed out by using ANOVA analysis using SPSS Version 21. The results of this research show that Time Pressure and Etical Awareness do not have significant influences towards the premature audit prosedures sign off with significant value 0,440 and 0,075. The other variables such as Audit Risk, Materiality,Locus Of Control, and Review Procedure and Quality Control to toward the premature audit prosedures sign off with significant value 0,005, 0,002, 0,000, and 0,002.Keywords : Audit, quality, materiality, etical, and premature